Queer Indigenous screen representation:beyond a gift from the past or a problem to be solved - O'Sullivan, Sandy; Reardon-Smith, Han; Blakers, Alana; Miller, Teyah (AlterNative: An International Journal of Indigenous Peoples, 2024)
Indigenous characters on screen have often been positioned as a gift from the past with innate heroic characteristics, or a problem to be solved in the form of the sad Indigenous person who cannot rise above colonial rule. That these archetypes are framed as positive in their representation is at odds with the need to have representations of the complexity of First Nations peoples. With queer Indigenous representation, characters become reduced to type, frequently reduced to representations of belligerence and difference, or unsubtle complexity that would be challenged in a non-Indigenous queer character. In this article and through the findings of our project Queer As. , we argue that this results in fewer Indigenous characters named as queer, we discuss some of the difficulties of casting and being cast as these characters, and we interrogate how the presence of queer Indigenous characters can deliver a more complete retelling of the world.